Immunization of rabbits with purified RNA polymerase I induces a distinct population of antibodies against nucleic acids as well as anti-RNA polymerase I antibodies, both characteristic of systemic lupus erythematosus. - Stetler, D A (1985)
Rabbits were immunized with either RNA polymerase I or poly(A) polymerase that had been purified to apparent homogeneity and was devoid of nucleic acids. Sera from rabbits thus immunized were screened for antibodies against nucleic acids. All seven rabbits injected with RNA polymerase I but none of the four rabbits immunized with poly(A) polymerase produced anti-nucleic acid antibodies. Anti-RNA polymerase I antibodies were induced after a single injection of the enzyme. Anti-polynucleotide antibodies were not detectable until after the second immunization. Anti-RNA polymerase I antibodies could be detected with as little as 100 pg of purified RNA polymerase I in the radioimmunoassay. At least 50 ng of poly(A) or 200 ng of DNA was required to detect anti-nucleic acid antibodies. The immunoreactivity of anti-RNA polymerase I antisera was greater with synthetic polynucleotides than with DNA, particularly early in the immunization schedule. Alkaline phosphatase treatment of poly(A) to remove 5' phosphates nearly abolished its antigenicity with respect to the early sera and decreased antibody binding of later sera by 60%. These results indicate that the anti-nucleic acid antibodies produced early were primarily directed against determinants including the 5'-terminal phosphates while antibodies produced later were directed against other sites. The antinucleic acid antibodies and anti-RNA polymerase I antibodies formed two distinct populations that were not immunologically crossreactive. We suggest that after injection, RNA polymerase I becomes associated with the nucleic acids present in blood plasma which renders them immunogenic; thus, association of nucleic acids with autoimmunogenic RNA polymerase I may be one of the mechanisms by which anti-DNA antibodies are induced in systemic lupus erythematosus.